PERAN MOTIVASI DAN PRAKTIK KOMUNIKATIF DALAM PENGUATAN KEMANDIRIAN SOSIAL PENYANDANG DISABILITAS NETRA DI SENTRA TERPADU PANGUDI LUHUR (STPL) BEKASI TIMUR - Serepina Tiur Maida; Ojakma Sihar Panaili Tumanggor; Kerlima Hutagaol; Sitti Wardiningsih; Muh Amin Saleh; Yudha Kartika; Frans Rommy Pelleng (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to analyze how people with visual impairments express their motivation through communicative actions in building social independence within digital spaces. Grounded in Motivation Action Theory (Heckhausen & Heckhausen, 2018), communication is understood as a goal-directed motivated action situated in social contexts. The research employs a qualitative content analysis design, examining open-access digital materials such as public podcasts, YouTube channels of disability organizations, online news portals, and inclusive digital campaigns that represent the communicative practices of visually impaired individuals. The analysis focuses on identifying motivational patterns, communicative strategies, and the meanings embedded in textual, audio, and visual content. The findings reveal four primary motivational drives behind their communicative actions: (1) strengthening public awareness, (2) demonstrating personal competence, (3) building community solidarity, and (4) expanding social and economic independence. Digital communication serves as a strategic medium for asserting identity, challenging stigma, and reinforcing social autonomy. Theoretically, this research extends the application of Motivation Action Theory within disability communication studies. Practically, it contributes to the development of more inclusive public communication strategies and media policies for people with visual impairments in Indonesia..